Unlocking Early Detection and Intervention Potential: Analyzing Visual Evoked Potentials (VEPs) in Adolescents/Teenagers with Narcotics Abuse Tendencies from the TelUnisba Neuropsychology EEG Dataset (TUNDA) - Wijayanto, Inung; Sulistyo, Tobias Mikha; Nur Pratama, Yohanes Juan; Safitri, Ayu Sekar; Rahmaniar, Thalita Dewi; Sa’idah, Sofia; Hadiyoso, Sugondo; Wibowo, Raiyan Adi; Kurnia Ismanto, Rima Ananda; Putri, Athaliqa Ananda; Khasanah, Andhita Nurul; Diliana, Faizza Haya; Azzahra, Salwa; Gadama, Melsan; Utami, Ayu Tuty (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA, 2024)
Narcotics abuse has extensive negative impacts on individuals, families, and society, including physical harm to organs and mental health disorders. Addressing teenage narcotics problems requires collaborative efforts involving educational institutions, families, and psychologists. Currently, narcotics has increasingly targeted teenagers, becoming a serious issue that demands special attention in prevention and treatment. Handling narcotic problems at the adolescent level necessitates close collaboration among educational institutions, families, and the community, including psychologists. Emphasizing the importance of early detection and prevention, this study proposes a method to detect the possibility of narcotic abuse in adolescents using the Go/No-Go Association Task (GNAT) test designed by psychologists. The study introduced the TelUnisba Neuropsychology EEG Dataset (TUNDA), an open EEG dataset with data on the emotional and habitual aspects of drug abuse in Indonesia, classified into